6v-105=25v+18

Simple and best practice solution for 6v-105=25v+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6v-105=25v+18 equation:


Simplifying
6v + -105 = 25v + 18

Reorder the terms:
-105 + 6v = 25v + 18

Reorder the terms:
-105 + 6v = 18 + 25v

Solving
-105 + 6v = 18 + 25v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-25v' to each side of the equation.
-105 + 6v + -25v = 18 + 25v + -25v

Combine like terms: 6v + -25v = -19v
-105 + -19v = 18 + 25v + -25v

Combine like terms: 25v + -25v = 0
-105 + -19v = 18 + 0
-105 + -19v = 18

Add '105' to each side of the equation.
-105 + 105 + -19v = 18 + 105

Combine like terms: -105 + 105 = 0
0 + -19v = 18 + 105
-19v = 18 + 105

Combine like terms: 18 + 105 = 123
-19v = 123

Divide each side by '-19'.
v = -6.473684211

Simplifying
v = -6.473684211

See similar equations:

| -5(6a-3)= | | -2+-2=1.2p+.25p | | 6a^6-42a^5-108a^4=0 | | c-59=-7 | | 2y=4-2x | | 7(-4m-6)=8m+6(2-3m) | | -19.1=x-1.9+x | | .5(s+9)=39 | | 42x^9-147x^7=0 | | 5b=-15+8b | | 6-(4y+1)=5(y+1)-y | | 6(t-1)=9(r-4) | | 1.6(d+-2)=40 | | y^2-3x-6y=8 | | 15y^2+29y+12= | | 49-54= | | 9x+2(x-1)=11x+8 | | 3(2x-1)+x=-x-3 | | 8k+k-7-10k= | | 3(2x+4)+6=2(x-5) | | 42m=999 | | 4-3x=26 | | 3x^2+17x+8= | | 42m=9999 | | 1000000+100000000000000000000000000000= | | 3(2x+4)+6=2x-5 | | 180=16r^2 | | 15=-9+x | | 9r^3-36r=0 | | =350-14x | | 20=-5y-3x | | -154x=6-3x |

Equations solver categories